2013
DOI: 10.1051/0004-6361/201321155
|View full text |Cite
|
Sign up to set email alerts
|

The GAPS programme with HARPS-N at TNG

Abstract: In the context of the programme Global Architecture of Planetary Systems (GAPS), we have performed radial velocity monitoring of the metal-poor star HIP 11952 on 35 nights during about 150 days using the newly installed high-resolution spectrograph HARPS-N at the TNG and HARPS at the ESO 3.6 m telescope. The radial velocities show a scatter of 7 m s −1 , compatible with the measurement errors for such a moderately warm metal-poor star (T eff = 6040 ± 120 K; [Fe/H] = −1.9 ± 0.1). We exclude the presence of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
4
30
1
Order By: Relevance
“…Our results indicate that there is no evidence for these two planetary systems. Moreover, in the latter case, we confirm the results recently published by Desidera et al (2013) and Müller et al (2013), who have shown that there is no indication of giant planets orbiting HIP 11952.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicate that there is no evidence for these two planetary systems. Moreover, in the latter case, we confirm the results recently published by Desidera et al (2013) and Müller et al (2013), who have shown that there is no indication of giant planets orbiting HIP 11952.…”
Section: Introductionsupporting
confidence: 92%
“…As for HIP 13044, this discovery was very controversial since according to the core-accretion model, giant planets are not expected to be formed around such metal-poor star, as we discussed above. However, based on much higher quality data taken with HARPS-N, Desidera et al (2013) recently showed that there is no planetary system around HIP 11952 and that the RVs are flat, showing a small scatter at the 7 m s −1 level, which has also been confirmed by Müller et al (2013).…”
Section: Hip11952mentioning
confidence: 85%
“…Since its installation in Spring 2012 at the Telescopio Nazionale Galileo, HARPS-N has allowed the obliquity of the transiting planet Qatar-1 b to be measured (Covino et al 2013) and has shown that the metal-poor star HIP 11952 does not harbor giant planets (Desidera et al 2013). The two new planets KOI-200 b and KOI-889 b presented here are the first to be detected and characterized with HARPS-N. Our observing program managed jointly with SOPHIE and HARPS-N shows the benefits that could be obtained for the follow-up of transiting planet candidates from coordinated observations secured with two spectrographs with different sensitivities, precisions, and accessibilities.…”
Section: Resultsmentioning
confidence: 99%
“…We have used five years of high-precision Doppler monitoring with the High Accuracy Radial velocity Planet Searcher for the Northern emisphere (HARPS-N) high-resolution (resolving power R ∼ 115 000) optical echelle spectrograph (Cosentino et al 2012) at the Telescopio Nazionale Galileo (TNG), combined with 15 yr of archival RVs data from the Lick-Carnegie Exoplanet Survey (LCES) HIRES/Keck Precision Radial Velocity survey (Butler et al 2017). The HARPS-N data were collected as part of the Harps-n red Dwarf Exoplanet Survey (HADES) programme, a collaboration between the Italian Global Architecture of Planetary Systems (GAPS; Covino et al 2013;Desidera et al 2013;Poretti et al 2016) Consortium 2 , the Institut de Ciències de l'Espai de Catalunya (ICE) and the Instituto de Astrofísica de Canarias (IAC). We also confirm the presence and update the amplitude of the Gl15A b RV signal, significantly reducing its minimum mass, while confirming the orbital period measured by Howard et al (2014).…”
Section: Introductionmentioning
confidence: 99%